Kearns-Sayre syndrome with facial and white matter extensive involvement: a (mitochondrial and nuclear gene related?) neurocristopathy? - Agostino Berio; Attilia Piazzi; Carlo Enrico Traverso (PAGEPress Publications, 2017)
The Authors report on a patient with Kearns-Sayre syndrome, large mtDNA deletion (7/kb), facial abnormalities and severe central nervous system (CNS) white matter radiological features, commonly attributed to spongy alterations. The common origin from neural crest cell (NCC) of facial structures (cartilagineous, osseous, vascular and of the peripheral nervous system) and of peripheral glia and partially of the CNS white matter are underlined and the facial and glial abnormalities are attributed to the abnormal reproduction/migration of NCC. In this view, the CNS spongy alterations in KSS may be not only a dystrophic process (leukodystrophy) but also a dysplastic condition (leukodysplasia). The Authors hypothesize that the symptoms may be related to mtDNA mutations associated to NCC nuclear gene abnormality. SOX 10 gene may be a nuclear candidate gene, as reported in some case of Waardenburg IV syndrome.